Updated database of the Middle Rio Grande, New Mexico - Novak, Susan, author; Julien, Pierre, author; Colorado State University, publisher (Colorado State University. Libraries, 2005)
The Middle Rio Grande Database was initiated in 1998. The database consists of measurements of discharge, channel characteristics and sediment for the period from 1895 to the present. The data for this project was obtained through the USGS and the USBR and was used in numerous Hydraulic Modeling reports written for the USBR. The database was updated with the most recent possible data, and was compiled and consolidated. The data and analyses developed during the last several years of research were organized into an interactive database that can be accessed like a webpage. Besides the database, numerous theses and dissertations on the Rio Grande have been compiled.
Hydrology days 2005
AGU hydrology days 2005
2005 annual AGU hydrology days was held at Colorado State University on March 7 - March 9, 2005.